Fintech in the time of COVID-19: Conceptual Overview - Candy Candy; Robin Robin; Estina Sativa; Sephia Septiana; Hansen Can; Alice Alice (Penerbit Goodwood, 2022)
Purpose: This study aims to analyze the relationship between financial technology (Fintech) and COVID-19. The importance of adopting 'digital' in all transaction could boost the Fintech growth during the pandemic. Fintech will help reduce the spread of COVID-19 by digital payment. Research methodology: This study uses a literature review study from 2020 to 2022—research data from international journals. Based on the research results, and opinions of previous researchers that expected to bring additional insights, references, and ideas. Results: COVID-19 influences the use of Fintech, which the positive impact resulting from this transformation in addition to providing convenience for users also brings economic development. Practical policies in Fintech encourage organizations to compete in offering financial services. Limitations: Researchers can conduct research on the development of Fintech in government infrastructure development and the communication networks between agencies in facilitating the community. Contribution: This study states that Fintech will help the economy to improvement and transformation so that it has a positive impact on all users. Thus, the presence of Fintech can positively influence developing countries such as Indonesia.